Pendidikan Kepramukaan Sebagai Ekstrakulikuler Wajib - Dwi Indah Pratiwi; Lukman Lukman; Sri Ken Kustianti (Universitas Bengkulu, 2021)
The research aims at knowing and describing the implementation of Scouting Education as a Compulsory Extracurricular According to the 2013 Curriculum at 48 Public Elementary Schools, Sindang Kelingi Rejang Lebong District. This research uses qualitative research, descriptive study method. The research subjects of the principal as Kamabigus, Class Teachers / Subject Teachers, and Scout Instructors. Research focus on the implementation of Scouting Education as a compulsory extracurricular activity. The research instruments were guidelines for observation, interviews, and documentation. Data collection techniques were observation, interviews, documentation, and triangulation. Data is analyzed through Data Collection, Data Display, Data Condensation, Consclusion Drawing / Verification. The research process is guided by five indicators of success, namely; (1) implementation of three models (Block Model, Actualization Model, and Regular Model), (2) Competence of school principals in the application of Scouting Education, class teachers / subject teachers as Scout Guards as Front Cluster Unit Guards, with the carrying capacity of education Scouting. The results of the research on the implementation of Scouting Education as a compulsory extracurricular activity at the 48 Rejang Lebong Public Elementary School are not in accordance with the 2013 curriculum rules. (1) the implementation of Scouting Education as a compulsory extracurricular activity at 48 Public Elementary Schools Sindang Kelingi Rejang Lebong Subdistrict only implements the Regular Model. (2) the implementation of Scouting Education as a compulsory extracurricular activity according to the 2013 curriculum at 48 Public Elementary Schools in Sindang Kelingi Rejang Lebong District has not been implemented according to the 2013 curriculum.